THE EFFECT OF ISLAMIC GOVERNANCE SCORE AND INVESTMENT ACCOUNT HOLDER ON THE DISCLOSURE OF ISLAMIC SOCIAL REPORTING AT ISLAMIC BANKS IN INDONESIA - Mais, Rimi Gusliana; Munir; Wulansari, Siti Sarah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This study aims to determine the effect of Islamic Governance Score (IG-Score) and Investment Account Holder (IAH) on Islamic Social Reporting (ISR) Disclosure. This research was conducted on Islamic banks registered with the Financial Services Authority for the 2016-2020 period and obtained 11 samples of Islamic banks. The method used is the panel data regression analysis method. The results showed that the IG-Score and IAH had an effect on the ISR design. IG-Score has an effect on ISR Disclosure, this shows that the presence of Shariah Supervisory Board (DPS) affects and encourages Islamic banks to carry out or improve ISR performance. IAH has an effect on ISR, in this case IAH determines compliance with Islamic banking principles and the consequences for ISR.